Age affects the contraction-induced mitochondrial redox response in skeletal muscle - Claflin, Dennis R.; Jackson, Malcolm J.; Brooks, Susan V. (Frontiers in Physiology, 2015)
Compromised mitochondrial respiratory function is associated with advancing age. Damage due to an increase in reactive oxygen species (ROS) with age is thought to contribute to the mitochondrial deficits. The coenzyme nicotinamide adenine dinucleotide in its reduced (NADH) and oxidized (NAD+) forms plays an essential role in the cyclic sequence of reactions that result in the regeneration of ATP by oxidative phosphorylation in mitochondria. Monitoring mitochondrial NADH/NAD+ redox status during recovery from an episode of high energy demand thus allows assessment of mitochondrial function. NADH fluoresces when excited with ultraviolet light in the UV-A band and NAD+ does not, allowing NADH/NAD+ to be monitored in real time using fluorescence microscopy. Our goal was to assess mitochondrial function by monitoring the NADH fluorescence response following a brief period of high energy demand in muscle from adult and old wild-type (WT) mice. This was accomplished by isolating whole lumbrical muscles from the hind paws of 7- and 28-month-old WT mice and making simultaneous measurements of force and NADH fluorescence responses during and after a 5 s maximum isometric contraction. All muscles exhibited fluorescence oscillations that were qualitatively similar and consisted of a brief transient increase followed by a longer transient period of reduced fluorescence and, finally, an increase that included an overshoot before recovering to resting level. Compared with the adult WT mice, muscles from the 28 mo WT mice exhibited a delayed peak during the first fluorescence transient and an attenuated recovery following the second transient. These findings indicate an impaired mitochondrial capacity to maintain NADH/NAD+ redox homeostasis during contractile activity in skeletal muscles of old mice.